Forecasting conservation impact to pinpoint spatial priorities in the Brazilian Cerrado. (December 2019) - Brum, Fernanda T.; Pressey, Robert L.; Bini, Luis Mauricio; Loyola, Rafael
Highlights: We forecast conservation impact of protected areas (PAs) in the Brazilian Cerrado. The conservation impact varied with PA management regime. Spatial priorities were located in the northern region of the Cerrado. Impact-based priorities can foster the interaction between science and policymaking. Abstract: Proper assessing the impacts of conservation interventions can create interaction spaces between researcher and implementation. For example, protected areas (PAs) are the main strategy to conserve biodiversity, but there is a widespread bias in their location towards unproductive and inaccessible lands. Thus, investments on PAs are likely to have been allocated to areas that did not need protection, at least in the short term, creating communication noise to the society. Here, we estimate the likely conservation impact of the recently established (2002–2012) PAs and indigenous lands (ILs) in a future scenario of land use projected to 2050. We selected areas that were similar to the PAs/ILs with positive conservation impact to propose spatial priorities aiming to minimize loss of Cerrado vegetation in the future. In our analyses, PAs in general and those of strict protection had significantly lower conversion rates than control areas, while sustainable use PAs and ILs showed no difference between control and protected areas. We did not find differences in impact values between PAs and ILs, but impact values were higher for strict protection than for sustainable use areas. We found a high density of potential priority areas to maximize impact in northern Cerrado. This region is the next agricultural frontier in the biome, having extensive vegetation cover that can be legally converted according to national legislation. By pinpointing conservation priorities based on impact, we can improve the benefit from land protection and increase the space of interactions between science, policymaking and society at large.